1994
DOI: 10.1002/hup.470090306
|View full text |Cite
|
Sign up to set email alerts
|

Self‐ratings by phobic patients during dental treatment: Greater improvement with nitrous oxide than midazolam

Abstract: The efficacy of intravenous midazolam and nitrous oxide inhalation at reducing self-rated mood and bodily symptoms was compared in patients referred to a dental sedation unit because their dental fears precluded treatment undrugged. Fifty-eight per cent of our patients could be randomly allocated to drug treatment, the others were assigned on clinical grounds. When they arrived for their first treatment, the clinically allocated patients (n = 40) were significantly more anxious, tense and restless than those r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
1
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
1
1
2
Order By: Relevance
“…We are therefore unable to separate out the contributions of each drug from the effect of having successfully received dental treatment. This contrasts with our previous finding of a clear superiority of nitrous oxide over midazolam in reducing the patient's seif-ratings of anxiety, when this was assessed during the gctsal treatment (Goodall et al, 1994). Whether the reductions in dental anxiety are of sufficient magnitude, and sufficiently long-lasting, to convey benefit for future dental treatment remains unknown.…”
Section: Discussioncontrasting
confidence: 90%
“…We are therefore unable to separate out the contributions of each drug from the effect of having successfully received dental treatment. This contrasts with our previous finding of a clear superiority of nitrous oxide over midazolam in reducing the patient's seif-ratings of anxiety, when this was assessed during the gctsal treatment (Goodall et al, 1994). Whether the reductions in dental anxiety are of sufficient magnitude, and sufficiently long-lasting, to convey benefit for future dental treatment remains unknown.…”
Section: Discussioncontrasting
confidence: 90%
“…For example, in a study that compared a BM approach with GA, it was found that BM was superior to GA in terms of reduction in dental anxiety scores (both self-reported and as rated by dentist) and led to less late cancellations and broken appointments (29). Another study, comparing NOS with IVS, found that reduction of distress during treatment was less for IVS patients than for NOS patients (30). Patients treated with concentrations of nitrous oxide gas utilized in dental fear clinics experience dental treatment fully conscious and are able to influence their own depth of sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Entre las disciplinas que se dedican a la prevención y tratamiento del miedo dental está la odontología conductual que aplica los principios teóricos, metodológicos y tecnológicos de la psicología conductual al ámbito extenso de la salud dental, pero principalmente a la prevención y tratamiento de la ansiedad dental y de los miedos dentales mediante la aplicación de múltiples técnicas orientadas al cambio conductual 3* . La utilización de las benzodiacepinas por diferentes vías de administración (oral, rectal, intranasal, intravenosa) es frecuente y sobradamente conocida en la prevención de estos problemas [14][15][16][17] . Otra alternativa es el uso de óxido nitroso que también se muestra eficiente en la prevención de estos sucesos 16,18 .…”
Section: Discussionunclassified
“…La utilización de las benzodiacepinas por diferentes vías de administración (oral, rectal, intranasal, intravenosa) es frecuente y sobradamente conocida en la prevención de estos problemas [14][15][16][17] . Otra alternativa es el uso de óxido nitroso que también se muestra eficiente en la prevención de estos sucesos 16,18 . Otros profesionales obtienen una reducción sustancial de la ansiedad y el miedo dental a través de sencillas sesiones de reestructuración cognitiva, modificando las ideas negativas que los sujetos tienen, perdurando en el tiempo la reducción del miedo conseguida 17,[19][20][21][22] .…”
Section: Discussionunclassified